Oral health in HPV-positive and HPV-negative patients with oropharyngeal squamous cell carcinoma - Kanzow, Philipp; Mielke, Katharina; Hrasky, Valentina; Wiegand, Susanne; Schliephake, Henning; Beutner, Dirk; Wiegand, Annette (Frontiers in Oncology, 2023)
This study compared oral health in oropharyngeal squamous cell carcinoma (OPSCC) patients with positive or negative human papillomavirus (HPV) status and analysed whether oral health was associated with survival. Patients referred for dental assessment prior to radio(chemo)therapy between 2009 and 2019 were included. Patient-related risk factors for OPSCC (alcohol, tobacco, HPV status), age, sex, treatment (primary treatment, intent), performance status, tumor/node/metastasis (TNM) staging, and oral health parameters (DMFT, periodontal status, teeth with/without root canal treatment and with/without periodontitis apicalis) were compared between HPV-negative and HPV-positive patients. Survival was assessed using Kaplan-Meier statistics. The effect of patient-related risk factors and oral health parameters was analysed by cox regression analyses (α=5%). A total of 119 patients (n=50 HPV-negative, n=69 HPV-positive) was included. HPV-positive patients showed more present teeth, a higher number of filled teeth, were less often edentulous and presented a lower DMFT compared to HPV-negative patients (padj.≤0.003). Among dentulous patients, HPV-positive patients showed more present teeth and fewer teeth with periodontitis apicalis lacking a root canal treatment (padj.≤0.036). Survival probability differed between groups (p=0.006) and trended towards being associated with HPV status, tobacco exposure, performance status, T stage, N stage, and the number of missing or filled teeth as well as the number of root canal treated teeth with periodontitis apicalis and the number of teeth with periodontitis apicalis lacking a root canal treatment (p≤0.077). However, only tobacco exposure, performance status, and the number of teeth with periodontitis apicalis lacking a root canal treatment in dentulous patients remained significant in the multivariate analyses (p≤0.047). HPV-negative patients with OPSCC showed a poorer oral health compared to HPV-positive patients, but survival was not associated with oral health.